Climate change and natural hazards in the Alps - Benjamin Einhorn; Nicolas Eckert; Christophe Chaix; Ludovic Ravanel; Philip Deline; Marie Gardent; Vincent Boudières; Didier Richard; Jean-Marc Vengeon; Gérald Giraud; Philippe Schoeneich (Revue de Géographie Alpine)
Under the effects of climate change, Alpine mountainous regions are undergoing fast and well-perceptible evolutions, which are attracting the growing attention of people, scientists and managers. To cope better with the hazards and vulnerabilities specific to these territories, the current national and European public policies in the Alpine countries now prescribe adapting natural hazard prevention to climate change. This paper provides a review of recent advances in knowledge on the perceived, measured and projected changes in i) climate patterns, ii) the cryosphere, hydrosystems and geomorphological dynamics on Alpine slopes, and iii) natural hazard evolution and induced risks at the scale of the French Alps. We give a brief overview of new results achieved by research, cooperation and capitalisation projects in these thematic fields during the programme period 2007-2013, which are available on databases, thematic knowledge platforms and observatories developed by different scientific and technical operators in the larger framework of the European Alpine arc. We illustrate this renewed synthesis by published examples of hydro-gravitational hazard activity chronicles, along with climate patterns identified as “predictors”.